Theoretical, Institutional and Ethical Basis for Implementing Modern Industrial Policy. Part I - Romanova, Olga Aleksandrovna; Ponomareva, Alena Olegovna (Economy of Regions, 2019)
The article demonstrates the states growing responsibility in making management decision in the context of the world and national economies’ unstable development. Industrial policy is one of the key instruments for implementing managerial decisions. We identified the notions of industrial policy (in a broad sense) and structural policy. Further, we classified concepts of industrial policy according to the scale of regulation subject and the states role in economy. The appearance of a network aspect of industrial policy focused on the concept of digital state (e-state) was noted. 200 years of industrial policy’s evolution demonstrate its constantly growing obligation to be the guarantee of social welfare. Nevertheless, in Russia legal understanding of industrial policy does not include any aspects of social guarantees. Therefore, we analyzed industrial policy theoretical foundations showing the necessity for its reconstruction using a theory of new structural economics. We established premises and tools for the theory’s successful realization. Industrial Development Fund plays an important role in implementing industrial policy’s priorities as a variety of important programs including “Industry digitalization” are financed by this organization. On the level of regional economics, different regional funds are involved in the process of structural transformations.